2018
DOI: 10.1055/s-0038-1670683
|View full text |Cite
|
Sign up to set email alerts
|

Management of Microsurgical Patients using Intraoperative Unfractionated Heparin and Thromboelastography

Abstract: The TEG is a useful adjunct for monitoring coagulation status in microsurgical breast reconstruction. When thrombosis at the anastomosis occurs, TEG correlates with a more rapid rebound from an intraoperative hypocoagulable state to a postoperative hypercoagulable state, when using the TEG. The TEG is a valuable tool for a more dynamic assessment of the patients' changing coagulation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Thromboelastography could be an interesting method to identify these high-risk patients. 8 The intraluminal application of heparin has also shown to reduce the thrombosis rate of anastomoses in an animal study. 9 Pérez et al 10 reported that local subcutaneous injection of heparin to be an effective alternative in improving flap venous congestion.…”
mentioning
confidence: 99%
“…Thromboelastography could be an interesting method to identify these high-risk patients. 8 The intraluminal application of heparin has also shown to reduce the thrombosis rate of anastomoses in an animal study. 9 Pérez et al 10 reported that local subcutaneous injection of heparin to be an effective alternative in improving flap venous congestion.…”
mentioning
confidence: 99%
“…Platelet levels, activated PTT (aPTT), and prothrombin time did not have predictive values for flap loss. 35 In patients undergoing free flap reconstruction for posttraumatic defects, higher flap loss rates have been observed in patients with pathological findings on preoperative rotational thromboelastometry (ROTEM), a similar measurement (13.6 vs. 4.3%). 36 Further analysis is needed to determine if these measurements can be combined with intraoperative evaluation of the local vasculature to further stratify patients at risk.…”
Section: Discussionmentioning
confidence: 91%
“…Thromboelastography [27], as a coagulation-monitoring method, which was widely used in the field of transplantation and blood vasculature operations [13, 28], monitors the dynamic process of coagulation and fibrinolysis. Zavlin et al [14] concluded that TEG is more dynamic compared to the APTT or PT, and is exceedingly reflective of real-time coagulation status changes. While these traditional coagulation tests were not able to identify patients with thrombosis in the fields of microsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboelastography (TEG), as a blood clotting test, which can monitor coagulation changes from clotting to fibrinolysis dynamically, was widely used in the field of transplantation and blood vasculature operations [1113]. TEG can simulate the whole process of coagulation and fibrinolysis in the human body environment, which is more sensitive than conventional coagulation assays in the evaluation of hypercoagulation, low coagulation, and fibrinolysis [1416].…”
Section: Introductionmentioning
confidence: 99%